Desain Penegakan Hukum Korupsi Partai Politik di Indonesia - Oktaryal, Agil; Hastuti, Proborini (Integritas : Jurnal Antikorupsi, 2021)
The large number of corruption cases whose funds flow to political parties becomes a problem when regulations cannot trap them. This brings awareness to create an ideal law enforcement design against criminal acts of corruption by political parties. As for the law enforcement design that initiated, reducing state financial assistance to the party; prohibition of participating in elections; and dissolution of political parties followed by restrictions on the rights of former officials to carry out political-based activities. This is accompanied by a broad and progressive interpretation by law enforcers to define political parties as corporations.